Innovation in the public sector : linking capacity and leadership - Bekkers, V. J. J. M.; Edelenbos, Jurian; Steijn, Abraham Jan, 1959- (New York : Palgrave MacMillan, 2011)
'Innovation in the Public Sector addresses issues relevant to an understanding of the innovation journeys on which public organizations have embarked. If public innovation is defined as a necessary condition for establishing meaningful interactions between the government and society, what are the relevant issues that may explain successful processes and forms of public innovation?'--
Includes bibliographical references (p. 223-241) and index.
Keywords: Organizational change; Administrative agencies -- Management